A new species of Leptogorgia (Coelenterata: Octocorallia: Gorgoniidae) from the shallow waters of the eastern Pacific - Breedy, O.; Guzman, H. M. (Zootaxa, 2005)
Leptogorgia cofrini, a new species of the family Gorgoniidae from Pacific Costa Rica and Panama inhabiting shallow waters (<25 m in depth) is described and illustrated. The small size, abundant, irregular branching, and the combination of long anthocodial rods, abundant large capstans, and a low occurrence of spindles in the coenenchyme are the main distinct characteristics of the new species. Mineralization of the axial skeleton is reported.